The Influence of Academic Supervision on Teacher Teaching Quality - Yunianto Nugroho, Dwi; Suherman, Suherman (Journal of English Language and Education, 2025)
This research aims to examine the extent of the impact of Academic Supervision on the improvement of learning quality. This research summarizes and analyzes previous studies to provide a comprehensive overview of the impact of academic supervision on the quality of learning. The method used in this research is a qualitative research method in the form of data analysis. (library rescarch). The data collection technique was carried out by systematically reviewing scientific literature, including journals, articles, books, and other sources. Where this research explains how Academic Supervision implemented in schools can improve the quality of classroom learning. This research examines 10 articles on the influence of academic supervision on the improvement of learning quality. The findings were processed through data collection, and then analyzed and described descriptively. And the results of this research indicate that efforts to improve the quality of learning through academic supervision can be successful if: (1) there is a paradigm shift from the principal and teachers regarding supervision, which initially viewed supervision as inspection, to supervision as a service to teachers aimed at improving learning. (2) there is good planning in the supervision process, including pre-supervision activities, during observation, as well as reflection and follow-up post-supervision, and leading to continuous improvement.